Barriers to the Use of Teaching Aids in Geography Subject in Primary Schools in Erbil City - Jwan Mohsin Rashid; Hadeia Mohammed Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The aim of this study is to investigate the barriers to the use of teaching aids in geography subject in primary schools in central Erbil, from the teachers' perspective. And to know their differences according to the (grinder, degree). The researcher used descriptive method and research community included all social worker and geography teachers in primary schools in central Erbil. The number of the teachers were (991) for the academic year (2021_2022). To achieve this goal, the researcher prepared a survey form for teachers. After ensuring the stability of the scale, the researcher implemented it on a sample of 150 teachers, 62 males and 88 females. After collecting the data and analyzing them, the researcher reached a statistical conclusion. As a result, the barriers to the use of teaching aids in primary schools in central Erbil in the subject of geography are high, there is no statistically significant difference at the level of (0.05) for the gender variable. And there is a statistically significant difference at the level of (0.05) for the qualification variable in favor of teachers with master’s degree or above.